Gambaran Pengalaman Peran Pengasuhan Ayah pada Perempuan Dewasa Awal dalam Menjalin Relasi Romantis - Kimberley Kimberley; Dewi, Fransisca Iriani Roesmala (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
The phenomenon f fatherly parenting plays a vital role in shaping the emotional and social experiences of daughters, particularly in forming romantic relationships. The role of fathers is often overlooked in parenting, even though it significantly influences the development of a daughter's personality and interpersonal relationships. Fathers who are emotionally involved can provide a sense of security, confidence, and an understanding of love. This study aims to describe the experiences of young adult women regarding their fathers' parenting roles and their impact on romantic relationships. This study adopts a phenomenological approach using purposive sampling techniques. The research was conducted over four months, and data were collected through interviews and observations. Five participants aged 18 to 25 years, with experiences of both positive and negative fatherly parenting and a history of romantic relationships, were involved in this study. The results show that positive fatherly parenting fosters positive romantic relationship experiences, such as the ability to build trust and intimacy. Conversely, hostile fatherly parenting leads to negative relationship patterns, such as distrust or a need for emotional validation. The lack of fatherly parenting also drives women to seek a father figure in others and to feel less trustful toward their partners. These findings demonstrate that the father's role in parenting has a significant impact on young adult women's romantic relationships.